1991
DOI: 10.1123/pes.3.2.111
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Age and Sexual Maturation on Children’s Blood Lactate Responses to Exercise

Abstract: A total of 100 boys and 91 girls, ages 11 to 16 years, completed a discontinuous treadmill test to voluntary exhaustion to determine the oxygen uptake/blood lactate relationship. Maturational stage was assessed in 72 boys and 47 girls using Tanner’s indices. Mean blood lactate at peak VO2 was significantly higher in the girls compared to the boys (6.1 vs. 5.8 mmol•l-1, P<0.01). Lactate at peak VO2 and percent peak VO2 at 4.0 mmol•l-1 were not significantly correlated with chronological age (p>0.05) in ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…Several cross-sectional studies have confirmed the pattern of progressively increasing peak blood lactate levels as children grow [1,3,4]. Some investigators have found that peak blood lactate levels are significantly higher in girls than in boys, whereas others have failed to confirm these results [3,24].…”
Section: Onset Of Blood Lactate Accumulationmentioning
confidence: 89%
See 3 more Smart Citations
“…Several cross-sectional studies have confirmed the pattern of progressively increasing peak blood lactate levels as children grow [1,3,4]. Some investigators have found that peak blood lactate levels are significantly higher in girls than in boys, whereas others have failed to confirm these results [3,24].…”
Section: Onset Of Blood Lactate Accumulationmentioning
confidence: 89%
“…This is particularly true for children because the peak percentage VO 2 corresponding to 2.5 mmol/L decreases from about 90% to 80% from 12 to 15 years of age [24], suggesting lower lactate values at the inflexion point for younger children. Using any value for all ages during growth makes it difficult to compare AT values that have been obtained and used in adult studies.…”
Section: Onset Of Blood Lactate Accumulationmentioning
confidence: 95%
See 2 more Smart Citations
“…Studies have consistently demonstrated that the lactate threshold (TLAC) expressed as per cent peak oxygen uptake (peak VO 2 ) is negatively correlated with age 22 23. A positive relationship between age and peak BLa is generally24 25 but not always22 observed.…”
Section: Muscle Biopsy Studiesmentioning
confidence: 99%